2012
DOI: 10.1186/1471-2458-12-357
|View full text |Cite
|
Sign up to set email alerts
|

A successful model of road traffic injury surveillance in a developing country: process and lessons learnt

Abstract: BackgroundRoad Traffic Injuries (RTIs) are one of the leading causes of death and disability worldwide with 90% of global mortality concentrated in the low and middle income countries. RTI surveillance is recommended to define the burden, identify high risk groups, plan intervention and monitor their impact. Despite its stated importance in the literature, very few examples of sustained surveillance systems are reported from low income countries. This paper shares the experience of setting up an urban RTI surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 6 publications
1
43
0
Order By: Relevance
“…Within the department of Emergency Medicine at the University of New Mexico, a medical resident used analysis of unintentional gunshot fatalities and their associated risk factors to inform the work of the New Mexico Zero Tolerance Team. This community action team which included HS, LE, medical and other stakeholders used a map of childhood firearm deaths to focus community resources on addressing youth firearm fatality prevention 39. Doezema similarly described how a medical resident’s participation in a death review team for domestic violence-related homicide victims resulted in more complete case reports 40…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the department of Emergency Medicine at the University of New Mexico, a medical resident used analysis of unintentional gunshot fatalities and their associated risk factors to inform the work of the New Mexico Zero Tolerance Team. This community action team which included HS, LE, medical and other stakeholders used a map of childhood firearm deaths to focus community resources on addressing youth firearm fatality prevention 39. Doezema similarly described how a medical resident’s participation in a death review team for domestic violence-related homicide victims resulted in more complete case reports 40…”
Section: Resultsmentioning
confidence: 99%
“…In Pakistan, LE and physicians collaborated to create and implement a LE-led Emergency Medical Systems (EMS) programme called Rescue 15 46. A different Pakistani programme, in the city of Karachi, established a partnership between hospitals, LE agencies, industry and media and developed a road traffic injury surveillance system and safety-focused road design 39. In addition, HS-LE partnerships are described that expanded to include other stakeholder groups (eg, businesses, insurance providers)39 43 in efforts to develop road traffic injury surveillance partnerships,45 as well as to address injury risk factors like teen driving44 and alcohol consumption 45…”
Section: Resultsmentioning
confidence: 99%
“…[11] None of the previous international and national reports had compared the sub-national variations of RTF indicators in Pakistan. [14–16]…”
Section: Methodsmentioning
confidence: 99%
“…A total of 90% of road traffic deaths occur in low-income and middle-income countries. These countries have 82% of the world's population and only have 54% of the world's registered vehicles (7,8). Statistics have shown that 30% to 40% of the deaths and injuries in accidents are due to unauthorized speed in Iran (9).…”
Section: Introductionmentioning
confidence: 99%